Kierunki i przesłanki zmian ustroju sądów w PRL: [Trends and premises of changes in the structure of courts in the Polish People's Republic] (Studia Prawnicze / The Legal Studies, 1983)
The structure of courts was defined by legislative acts of 1960s, in 1970s it underwent partial and not always compact modifications. Setting up the Chief Administrative Court in 1980 was a new reform because it not only extended the jurisdiction of courts but also - submitting the legality of administrative policy :and administrative legislation to the CAC control - it united courts with the issues of current politics.Substantial changes were also introduced in the Years 1980-1982. Although, especially at the beginning, they had some fortuitous 'character, being a derivative of political controversies, however an opinion was established that all kinds of disputes with a citizen as a party and also some other kinds of disputes (collective disputes, self-government disputes) should be examined by the court. At the same time new legislation charged the courts with examining many cases with clear political connotations, which may impair the independence of judges.The plans on the reform of the structure of courts have not been settled .and the author deals with these issues.As far as the structure of courts is concerned, first of all the system of courts - at a province level should be reorganized by separating the courts from the administrative division of the country and reducing their number. This will enable to set up adequately staffed and independent of local authorities supraprovince courts. Then extending jurisdiction of the new courts will be possible by means of including new disputes which so far have not been examined by courts and taking over disputes which so far have been examined by special courts. First of all, ordinary courts should take over jurisdiction of labour and social insurance courts, and, then of state economic arbitration. Administrative courts, however should not be abolished.As regards the guarantee of independence of judges three problems should be pointed out: 1) strengthening personal guarantees of independence, which is connected with a postulate to generalize the principle of appointing judges for an indefininte period; this should also refer to the Supreme Court judges, and introducing some changes into the catalogue of premises on the deprivation of the post, 2) explanation of the relation of a judge to provisions which are contrary to the legal norms of a higher rank - as regards unconstitutional laws - Constitutional Tribunal should be set up, 3) danger resulting from charging judges with examining disputes too closely connected with politics.